Factors Involved In First Myocardial Infarction, Its Complications And Thrombolytic Pattern In Selected Hospitals Of Nepal - Shah, R.K.; Upadhayaya, AB; Tibrewala, L.P.; Regmi, P.R.; Acharya, K.P.; Khanal, HH; Rajbhandari, S; Shrestha, D; Shrestha, U; Pandey, M (Nepalese Heart Journal, 2004)
World Health Organization [WHO] has predicted that by AD 2020 up to three- quarter of death in developing countries would result from non-communicable diseases (NCDs) and that Coronary Heart Disease (CHD) will top the list of killers. Data also indicate that epidemiological transition, which is characterized by aging and changing life style and culminates in epidemics of hypertension (HTN) and CHD, is rapidly occurring in India and other developing countries.